2008
DOI: 10.1038/sc.2008.96
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting alteration patterns of different cartilage plates in knee articular cartilage after spinal cord injury in rats

Abstract: Study design: Experimental, controlled trial, animal study. Objective: To assess morphologic changes in different cartilage plates after spinal cord injury and identify the localization of these alterations. Setting: Saitama, Japan. Methods: A total of 16 Wistar rats were used. Eight rats underwent a spinal cord injury and eight rats had no intervention as control. The cartilage alterations of the knee joint were evaluated with radiography and histomorphometric analysis. To quantify cartilage alterations, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…The lower limb joints are unloaded and restricted in movement in animals and in humans with spinal cord injuries [23]. Previous studies have shown thinning of the rat knee cartilage 4 weeks after a spinal cord injury [22,23]. However, in the current study, cartilage thickness remained unchanged and no effect of stretching was detected.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…The lower limb joints are unloaded and restricted in movement in animals and in humans with spinal cord injuries [23]. Previous studies have shown thinning of the rat knee cartilage 4 weeks after a spinal cord injury [22,23]. However, in the current study, cartilage thickness remained unchanged and no effect of stretching was detected.…”
Section: Discussioncontrasting
confidence: 50%
“…Mechanical overload induces VEGF [29] and therefore mechanical stress by stretching may stimulate VEGF expression. However, we previously reported vascular invasions of the subchondral bone penetrating the cartilage 4 weeks after a spinal cord injury [22,23]. VEGF encourages vascular tissue formation from bone marrow into the articular cartilage [29,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations